ANALISA PENGARUH PEMBEBANAN TERHADAP EFISIENSI AUXILIARY TRANSFORMATOR PT.KAI LRT SUMSEL - marniati, yessi - (Jurnal Tekno, 2021)
The efficiency level of the transformer becomes a benchmark to determine the optimal performance of the equipment. The percentage of transformer efficiency values ​​is obtained from the calculation of input power data, output power and transformer losses. Based on the results of the discussion, the percentage of efficiency and losses generated by the 50kVA Auxiliary Transformer at the DSS Station of PT. KAI LRT Sumsel at the time of peak load, the highest efficiency value was 92.56% and the total loss was 1644.20W for the lowest efficiency value, which was 92.30% and the total loss was 1701.08W. When the load is average, the highest efficiency value is 92.73% and the total loss is 1604.83W. Meanwhile, the lowest efficiency value was 92.56% and the total loss was 1293.20W. At the lowest load condition, the highest efficiency value is 92.72% and the total loss is 1606.63W. Meanwhile, the lowest efficiency value was 91.92% and the total loss was 1784.88W. The higher the transformer losses, the smaller the percentage of efficiency. The higher the efficiency of the transformer, the better its performance. Good performance will make the role of the transformer in the power distribution system more efficient so that electrical energy can be channeled optimally.